Impact of low-carbohydrate diet on renal function: a meta-analysis of over 1000 individuals from nine randomised controlled trials. Issue 4 (27th June 2016) - Oyabu, Chikako; Hashimoto, Yoshitaka; Fukuda, Takuya; Tanaka, Muhei; Asano, Mai; Yamazaki, Masahiro; Fukui, Michiaki
Abstract: We aimed to clarify the effect of low-carbohydrate diet (LCD) on renal function in overweight and obese individuals without chronic kidney disease (CKD). Literature searches were performed using EMBASE, MEDLINE and Cochrane Library until December 2015. We selected articles that reported human studies from their inception until December 2015 in English using the following searching terms: 'Low carbohydrate diet' AND ('Clinical trial' OR 'Clinical study' OR 'Clinical investigation' OR 'Observational study' OR 'Cohort study'). We compared the effects of LCD on renal function, defined as change in estimated glomerular filtration rate (eGFR), assessed in randomised-controlled trials. We calculated the mean change in eGFR and the mean change in standard deviations by eGFR or creatinine clearance, and compared the mean change in eGFR and standard deviations in LCD with those in the control diet using fixed-effects models. We selected nine randomised controlled trials including 1687 participants (861 were fed LCD and 826 were fed the control diet). The mean change in eGFR in the LCD group was −4·7 to 24·0 ml/min per 1·73 m 2 and that in the control diet group was −4·1 to 10·8 ml/min per 1·73 m 2 . The mean change in eGFR in the LCD group was greater than that in the control diet (0·13 ml/min per 1·73 m 2 ; 95 % CI 0·00, 0·26). In the present meta-analysis, we identified that the increase in eGFR was greater in LCD compared with the control diet in overweight and obese individuals without CKD.